الاحتراق النفسى وعلاقته بالصلابة النفسية لدي أساتذة التعليم الابتدائي - بكاري,بوبكر; بن دانية,محمد الاخضر (University of Eloued جامعة الوادي, 2024)
هدف البحث الحالي الى الكشف عن علاقة الاحتراق النفسي بالصلابة النفسية لدى عينة من أساتذة التعليم في الطور الابتدائي لكل من ولايتي تقرت والوادي التابعين للقطاع العام كما هدفت الدراسة الى التعرف على طبيعة العلاقة بين الاحتراق النفسي و الصلابة النفسية لدى افراد العينة و كدلك الكشف عن دلالة الفروق بين افراد العينة في الاحتراق النفسي و الصلابة النفسية تبعا لمتغير المنطقة و متغير الجنس )ذكور,اناث (وقد تكونت العينة من(140) استاد و استاذة اختيروا بطريقة عشوائية، وطبقت عليهم أداتي: مقياس الاحتراق النفسي "لماسلاش" ومقياس الصلابة النفسية "لعماد مخيمر" والدي تم تقنينه على حسب البيئة الجزائرية من طرف "بشير معمرية" تم استخدام المنهج الوصفي الارتباطي، وبعد التأكد من الخصائص السيكو مترية و تم أجراء الدراسة الميدانية فكانت النتائج كالاتي: • لا توجد علاقة ذات دلالة إحصائية في الاحتراق النفسي والصلابة النفسية لدى أساتذة التعليم الابتدائي. • لا توجد علاقة ذات دلالة إحصائية في الاحتراق النفسي والصلابة النفسية بين أساتذة تقرت والوادي. • لاتوجد فروق ذات دلالة إحصائية بين الجنسين من الأساتذة في الاحتراق النفسي والصلابة النفسية. The current study attempt to explore the relationship, between psychological burnout and psychological hardiness, among primary education teachers in both the states of Oued Souf and Touggourt in the public sector, it also amis to identify the correlation and the difference between the teachers of both states in psychological burnout and psychological hardiness as well as the statiscal signification of the difference between the genders of teachers in burnout and psychological hardiness . To answer the questions of the study and verify its hypotheses, the researchers relied on the descriptive correlative approach, with the aim relationship between burnout and psychological hardiness, among primary education teachers in order to collect the study data the burnout inventory MBI “ Christina Maslach” and “ImadeMukhaimer” calcified by “BashhirMaamria” on the Algerine environment Moreover the study sample consisted of (140 ) primary education teachers who were chosen intentionally for data collection and analysis statiscal analysis, the statistical packages for social sciences (spss) program was used by using a set of statiscal methods to verify the results of the study including the Pearson correlation coefficient to determine the significance of the relationship coefficient to determine the significance of the relationship between the various variables the mean and standard deviation as well a
Keywords: الإحتراق النفسي; الصلابة النفسية; psychological burnout; psychological toughness